Crisis Communication Strategy of the Ministry of Finance in the Case of Children of Tax Officials - Maulana, Mahesa; Nurulhuda, Isthikana; Aisyah, Siti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
In an organization, a crisis is considered a negative event that has the potential to affect the organization or company. The Ministry of Finance as one of the state institutions is not free from problems, starting with the case of the beating of the son of a tax official (Rafael Alun Trisambodo). This research aims to reveal the crisis communication strategy carried out by the Ministry of Finance. This study uses a qualitative method. The data collection technique in this research uses literature studies and documentation studies via online media, namely kompas.com and detik.com with a time span of 20 February 2023 to 17 April 2023. The data analysis technique used by researchers is descriptive narrative. The results of this research show that the Ministry of Finance is experiencing a crisis, so several crisis communication strategies have been implemented, such as admitting mistakes, apologizing, and openness/transparency. The crisis communication strategy implemented by the Ministry of Finance, was able to reduce public anger. This research can be a reference, especially on crisis communication, namely by analyzing public relations responses.